ABOUT THE BASICS OF COMPREHENSIVE GERIATRIC ASSESSMENT - L. M. Farkhutdinova (Архивъ внутренней медицины)
The article covers the principles of comprehensive geriatric assessment — an interdisciplinary diagnostic procedure aimed at developing a plan of treatment, long-term monitoring and support of an elderly person. The components of a comprehensive geriatric assessment, including the determination of physical, functional, psychological and social status of the subject, are reflected. During the process of analyzing the patient’s physical status, the age-related features of the functioning of various organs and systems, knowledge of which is necessary for the development of a targeted geriatric care strategy, should be taken into account. Involution of the respiratory organs is characterized by a decrease in the respiratory surface, atrophic processes in the mucous and lymphoid tissues, and an increased risk of developing bronchoobstructive syndrome. Degenerative sclerotic changes in the cardiovascular system contribute to the development of circulatory failure, sinus node dysfunction, increased sensitivity to stress factors, orthostatic hypotension, etc. With age, the secretory function of the gastrointestinal tract decreases, and the functional ability of the liver is limited. Reducing the reserve capacity of the kidneys provokes the development of inflammatory processes and contributes to the dehydration of the body. In older people, the risk of developing diabetes, hypothyroidism and hyperparathyroidism increases. The growth of connective tissue in the blood-forming organs limits the functionality of the blood system. Age-related changes in the musculoskeletal system are characterized by a decrease in muscle mass and the development of osteoporosis. Drug therapy is also being analyzed, since polypharmacy in the elderly is associated with a particularly high risk of developing side effects of the drugs. Assessment of the functional status implies the determination of the self service ability and the degree of a person’s independence from the help of others by his/her ability to perform basic functions, activities in everyday life and instrumental activity. The psycho emotional status is judged by the emotional background of the patient and his/her cognitive functions. Social and household status is estimated by the living conditions of an elderly person. Based on the results of a comprehensive geriatric assessment, an individual management plan is drawn up, the implementation of which is possible with the combined efforts of the geriatrician and a team of medical specialists, relatives, and social workers.